THE INFLUENCE OF SERVICE QUALITY FOR SATISFACTION LEVEL AMONG INDONESIAN WORKERS IN MALAYSIA - Rozamuri, Arif Murti (Faculty of Economic and Business, University of Pasundan, 2023)
Indonesian workers one of the highest employees in Malaysia. Although complementing one another, managing the Indonesian workforce is not without challenges. Among them is the type of work not in accordance with the employment agreement, over time work with no additional allowance, termination of employment and repatriation of employees without their rights granted. Therefore, the main point of this study is to analyze the effect of service quality on Indonesia's level of satisfaction. This is to see the extent of the influence of dimension of tangibles, reliability, responsiveness, assurance, and empathy towards employee satisfaction. This study was conducted using quantitative methods, while the respondents were Indonesian workers in Malaysia in the services and manufacturing sectors. This study shows that 5 dimensions of service quality have an influence on the level of satisfaction. However, the dimension of responsiveness has a big impact on Indonesia's level of job satisfaction.